COVID-19 and the quality of mathematics education teaching and learning in a first-year course - Mbhiza, H.; Muthelo, D. (South African Journal of Higher Education, 2022)
This article is vested on the need for higher education educators to be reflective on their practices in order to configure effective ways to interact with the students and knowledge for specific courses. It is uncontested that education systems globally are under constant pressure to respond to the changing needs of societies. The outbreak of COVID-19 has reminded us that the complexity of education needs responsive practices to facilitate effective teaching and learning across all levels of schooling globally. All over the world, the normative ways of teaching and learning evolved drastically in the first quarter of the 2020 academic year when teachers and students found online offerings to be the dominant option available as a sequel to the pandemic conditions. In South Africa specifically, students and teachers were thrust into virtual teaching and learning situations with the majority of them having no preparation for this shift. This article presents an auto-ethnographical account of the knowledge gaps in the teaching and learning of mathematics education in a first-year education course in an online space. We used auto-ethnography to discuss our experiences of teaching limits and continuity. We argue that teaching the topic on an online platform constrain student teachers’ procedural thinking, conceptual development, and demonstration of their thought processes during mathematics learning and assessment. We also discuss our experiences of developing assessment tasks for the topic and how students identified cheating mechanisms to answer questions in assessments.